Wild Ungulate Population in Baghmara Buffer Zone Community Forest, Nepal - Sharma, Bhuvan Keshar; Solanki, Ghana Shyam; Chalise, Mukesh Kumar (Journal of Natural History Museum, 2015)
This study was conducted in Baghmara Buffer Zone Community Forest aiming to find out the ungulate population. Total complete count method was utilized by direct visual counting technique. The enumerator covered the entire forest by walking along the fixed bearing from one end to another end of the forest counting all ungulates. The animals were stalked and approached with minimum disturbance, counting and sex were confirmed with the help of binoculars. The current study recorded five species of ungulates. There were 12 resident Barking Deer, 2 Hog Deer, 23 Sambar, 4 Wild Boar and 182 Spotted Deer. The number of wild ungulates increased significantly (T=2.01, p < 0.05, df=8) in post-community management regimes (n=224) than the pre-community management (n=1). J. Nat. Hist. Mus. Vol. 27, 2013: 66-71